Percentile-Range Indexed Mapping and Evaluation (PRIME): A new tool for long-term data discovery and application. (February 2020) - Dessu, Shimelis B.; Price, René M.; Kominoski, John S.; Davis, Stephen E.; Wymore, Adam S.; McDowell, William H.; Gaiser, Evelyn E.
Abstract: Percentile-Range Indexed Mapping and Evaluation (PRIME) is a new tool to visualize and quantifying spatio-temporal dynamics of long-term datasets. PRIME is based on categorical partitioning of magnitude based on user defined indices assigned to ranges of percentile and mapping subsets of data at selected percentiles of long-term data. Indices can reflect attributes such as water management decisions, tolerable range of water quality to a species, ecological risk, response to and recovery from disturbance, and values of ecosystem services. PRIME provides visual and robust datascapes and flexibility to evaluate variability in space and time for long-term environmental assessment. Here, we demonstrate the utility of PRIME using 16 years of hydrologic and salinity data from 14 sites representing three unique hydrological systems in the Florida Coastal Everglades (FCE). The resulting PRIME datascapes reveal interaction between water management and sea-level rise to drive salinity levels in the FCE. Highlights: Introduces PRIME, a new tool for synthesis and visualization of long-term data. PRIME provides a novel mapping strategy by scaling time series data to percentiles. PRIME allows for comparison among different types of datasets. PRIME is intended for both non-specialist users and experts.